Effective utilization of agricultural waste in synthesizing activator for sustainable geopolymer technology. (2nd January 2023) - Kallamalayil Nassar, Anoop; Kathirvel, Parthiban
Abstract: The creation of one-part geopolymer mixtures is necessary to increase the economic feasibility of geopolymers in practice. The utilization of extremely corrosive alkali solutions that are often used as activators in the development of standard geopolymers hinders the sustainability nature of geopolymers. Hence, to overcome the sustainability issues related to sodium silicate, a novel method of developing sodium silicate from rice husk ash (RHA) and using it as an activator in the development of one-part geopolymer binders has been proposed in this research. This novel sodium silicate has been produced in a thermo-mechano-chemical technique by agglomerating RHA with sodium hydroxide. The developed binders were characterized by mineral composition and phase, morphology, and strength parameters. The compressive strength results were in the range of 58.08 MPa to 88.23 MPa and varies with respect to the modulus of silica of the derived powdered activator. The enhanced polycondensation process and better gel structure, as seen by microstructural tests, are what account for the increase in mechanical strength. By this, it can be concluded that the activator powder derived in this research can be used to produce a geopolymer binder that can be handled similarly to Portland cement with less potential for global warming. Highlights: AAP has been synthesized from RHA using thermo-mechano-chemical technique. Synthesized AAP was used to activate one-part geopolymer with GGBFS as precursor. Fresh, hardened & microstructural characteristics of geopolymer paste were examined. This method significantly reduce environmental issues than conventional geopolymers. Resulting AAP can be handled similar to PC with less potential for global warming.